Bismuth oxyiodate composite piezoelectric hydrogel as well as preparation method and application thereof
By integrating BiOIO3 nanosheets into self-assembled stem cell bone marrow homing peptides, a bismuth iodate composite piezoelectric hydrogel is constructed, which solves the problem of difficulty in inhibiting the growth and recurrence of osteosarcoma tumors and restoring bone structure and function in the existing technology. Significant osteogenic induction and anti-tumor effects under ultrasound stimulation were achieved.
Patent Information
- Application Number
- CN202411459980.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-21
AI Technical Summary
It is difficult to develop a biological material that can not only inhibit the growth and recurrence of osteosarcoma tumors, but also maximize the restoration of bone structure and function.
By integrating the 2D BIOIO3 nanoil into the self -assembled stem cell bone marrow returning to the nest peptide, a composite voltage electrocarbon gel is constructed. effect.
The hydrogel can promote the production of reactive oxygen species, induce tumor cell apoptosis, and significantly improve the osteogenic capacity of bones under ultrasound stimulation, providing a new treatment strategy for osteosarcoma.
Smart Images

Figure CN119326957A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogel materials, and in particular to a bismuth oxyiodate composite piezoelectric hydrogel and a preparation method and application thereof. Background Art
[0002] Catalytic therapies that utilize reactive oxygen species (ROS) to induce apoptosis of tumor cells have been developed, including photocatalysis, piezocatalysis, and thermocatalysis. However, conventional photocatalysis has limited efficacy in treating tumors, mainly due to the poor tissue penetration of light. Piezocatalysis based on the piezoelectric effect provides a new therapeutic strategy. This method generates a piezoelectric potential to promote charge separation or transfer, thereby inducing redox reactions. Unlike laser irradiation, ultrasound, as an exogenous energy input to piezoelectric materials, has become a hot topic of research due to its advantages such as non-invasiveness and depth. Ultrasound has the ability to induce band bending inside piezoelectric nanomaterials, effectively promoting charge separation and transfer, thereby catalyzing redox reactions. Thermocatalysis based on temperature gradient-driven energy conversion is another promising tumor treatment method. Thermocatalysis enhances ROS generation and improves catalytic efficiency. Interestingly, ultrasound not only provides mechanical effects, but also thermal effects. However, there are relatively few studies on the simultaneous use of the mechanical and thermal effects of ultrasound in semiconductor materials.
[0003] Osteosarcoma is the most common primary bone malignancy, mainly affecting children and adolescents. It mainly occurs in long bones, such as the distal femur, proximal tibia, and humerus. In the past two decades, the 5-year survival rate of patients with localized tumors has been about 60-70%, while the 5-year survival rate of patients with recurrent or metastatic osteosarcoma is less than 25%. Bone defects caused by osteosarcoma usually require comprehensive treatment in clinical treatment, with the goal of maximally restoring the structure and function of the bone while controlling tumor growth and recurrence. Biologically, osteoclasts interact with osteosarcoma cells to form a vicious cycle that favors osteosarcoma growth and bone resorption. Although various regenerative reconstruction strategies, such as bone transplantation, artificial prosthesis replacement, stem cell implantation, and biological scaffolds, have been used to repair bone defects caused by osteosarcoma, clinical treatment progress is still limited due to the challenges of bone regeneration in the tumor microenvironment.
[0004] Related technology Chinese patent CN117883632A discloses a BaTiO3 composite piezoelectric hydrogel, including gelatin hydrogel and BaTiO3 nanoparticles uniformly dispersed in the gelatin hydrogel. By incorporating BaTiO3 nanoparticles into tilapia gelatin hydrogel with intrinsic anti-inflammatory potential, a wireless piezoelectric hydrogel is constructed as a biomaterial for preparing periodontal tissue / bone tissue repair. It can be used to prepare biomaterials for repairing bone defects induced by periodontitis and / or biomaterials for repairing bone defects induced by immune stimulation, and does not have anti-tumor effects.
[0005] Given the key regulatory roles of ROS and stem cell differentiation in bone healing and osteosarcoma pathology, there is an urgent need to develop biomaterials that can both inhibit tumor growth and recurrence and restore the structure and function of bones to the greatest extent. Therefore, it is crucial to develop a therapeutic technology that has both excellent anti-tumor effects and advanced osteogenesis. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a bismuth oxyiodate (BiOIO3) composite piezoelectric hydrogel and its preparation method and application. The bismuth oxyiodate composite piezoelectric hydrogel of the present invention can promote the generation of reactive oxygen species, induce tumor cell apoptosis, and exhibit significant osteogenic induction under ultrasonic stimulation.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a bismuth iodate oxygen composite piezoelectric hydrogel, which is prepared from raw materials including the following mass percentages:
[0009] The first self-assembling short peptide is 0.125% to 0.5%, the self-assembling stem cell bone marrow homing peptide is 0.125% to 0.5%, the BiOIO3 nanosheet is 0 to 0.02% and the mass percentage of the BiOIO3 nanosheet is not 0, and the solvent is 98.99% to 99.75%; the self-assembling stem cell bone marrow homing peptide is obtained by functionalizing the second self-assembling short peptide with the stem cell bone marrow homing peptide segment.
[0010] Preferably, the stem cell bone marrow homing peptide is a first peptide, a second peptide, a third peptide or a fourth peptide, the amino acid sequence of the first peptide is shown as SEQ ID NO.1, the amino acid sequence of the second peptide is shown as SEQ ID NO.2, the amino acid sequence of the third peptide is shown as SEQ ID NO.3, and the amino acid sequence of the fourth peptide is shown as SEQ ID NO.4.
[0011] Preferably, the first self-assembling short peptide and the second self-assembling short peptide are independently RAD16-I, EAK16-II, FF, VEVK or KLD-12, and the amino acid sequence of VEVK is shown in SEQ ID NO.5.
[0012] Preferably, the stem cell bone marrow homing peptide segment is the third peptide segment, and the first self-assembling short peptide and the second self-assembling short peptide are both KLD-12.
[0013] Preferably, the mass percentage of BiOIO3 nanosheets in the raw material is 0.005% to 0.01%.
[0014] Preferably, the particle size of the BiOIO3 nanosheets is 100-800 nm, the thickness is 2-6 nm, and the specific surface area is 10-20 m 2 / g.
[0015] Preferably, the solvent is PBS buffer, water or cell culture medium.
[0016] The present invention also provides a method for preparing the bismuth oxyiodate composite piezoelectric hydrogel described in the above technical solution, comprising the following steps:
[0017] Mixing the first self-assembling short peptide and the first solvent to obtain a self-assembling short peptide solution;
[0018] mixing the self-assembled stem cell bone marrow homing peptide with a second solvent to obtain a self-assembled stem cell bone marrow homing peptide solution;
[0019] The self-assembled short peptide solution, the self-assembled stem cell bone marrow homing peptide solution, the BiOIO3 nanosheets and the remaining solvent are mixed and then gelled to obtain the bismuth oxygen iodate composite piezoelectric hydrogel.
[0020] Preferably, the gelation is carried out under ultrasonic conditions, and the gelation time is 10 to 30 minutes.
[0021] The present invention also provides the use of the bismuth oxyiodate composite piezoelectric hydrogel described in the above technical scheme or the bismuth oxyiodate composite piezoelectric hydrogel prepared by the preparation method described in the above technical scheme in the preparation of anti-liver cancer drugs, drugs for inhibiting postoperative residual tumors, or drugs for repairing bone defects.
[0022] The invention provides a bismuth oxyiodate composite piezoelectric hydrogel, which is prepared from the following raw materials in mass percentage: 0.125% to 0.5% of a first self-assembling short peptide, 0.125% to 0.5% of a self-assembling stem cell bone marrow homing peptide, 0% to 0.02% of a BiOIO3 nanosheet and the mass percentage of the BiOIO3 nanosheet is not 0, and 98.99% to 99.75% of a solvent; the self-assembling stem cell bone marrow homing peptide is obtained by functionalizing a second self-assembling short peptide with a stem cell bone marrow homing peptide segment.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention constructs an injectable, degradable, and ultrasound-responsive piezoelectric hydrogel by integrating 2D BiOIO3 nanosheets (BiOIO3 NSs) into a self-assembled stem cell bone marrow homing peptide, wherein the BiOIO3 NSs exhibits significant piezoelectric catalytic performance. Under the action of ultrasound, the piezoelectric hydrogel generates electrical signals through mechanical and thermal effects. This unique physical property promotes the production of reactive oxygen species and induces tumor cell apoptosis, thus opening up a new way to regulate tumor cell behavior and having great potential in advanced cancer treatment and tissue engineering. The obtained bismuth iodate oxyiodate composite piezoelectric hydrogel exhibits significant biocompatibility, osteogenic induction, and anti-tumor effects under ultrasound stimulation, that is, the bismuth iodate oxyiodate composite piezoelectric hydrogel of the present invention is a biomaterial that can both inhibit tumor growth and recurrence and restore the structure and function of bones to the greatest extent, has a wide range of uses in the preparation of biomaterials that regulate tumor growth and promote the osteogenic ability of mesenchymal stem cells, has good application prospects in the biomedical field and in clinic, and provides a promising strategy for comprehensive osteosarcoma treatment.
[0025] The bismuth iodate oxyiodate composite piezoelectric hydrogel prepared by the present invention is a semi-solid gel (stable and non-flowing when inverted), and the solvent exists in various forms, which is not only a filler of the network structure, but also forms hydrogen bonds and electrostatic interactions with peptide chains, thereby promoting and stabilizing the formation of the gel. The solvent can diffuse freely in the gel network, adjust the physical properties of the gel, and affect its application in drug delivery, tissue engineering, etc. The behavior of the solvent is changed by external regulatory factors, and the mechanical strength and functional properties of the gel can be further controlled.
[0026] The present invention also provides a method for preparing the bismuth oxyiodate composite piezoelectric hydrogel described in the above technical solution. The preparation method of the present invention is simple to operate and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 TEM image of BiOIO3 NSs;
[0028] Figure 2 HRTEM image of BiOIO3 NSs;
[0029] Figure 3 is the XRD pattern of BiOIO3 NSs;
[0030] Figure 4 TEM images of each group of hydrogels;
[0031] Figure 5 Cryo-SEM image of KLD hydrogel;
[0032] Figure 6Cryo-SEM image of KLD@BiOIO3 NSs hydrogel;
[0033] Figure 7 Cryo-SEM image of PFS hydrogel;
[0034] Figure 8 Cryo-SEM image of PFS@BiOIO3 NSs composite piezoelectric hydrogel;
[0035] Fig. 9 The characteristic butterfly loop and phase hysteresis curves of BiOIO3 NSs under ±10V voltage;
[0036] Fig.10 is the rheological property curve of each group of hydrogels;
[0037] Fig.11 is the shear-dilution curve of each group of hydrogels;
[0038] Fig.12 Fluorescence microscope images of live / dead tumor cells after treatment with different conditions;
[0039] Fig.13 for the expression of genes related to early / late osteogenic differentiation;
[0040] Fig.14 Transverse (X), longitudinal (Y) and three-dimensional (3D) reconstructions of the tibiae of osteosarcoma-bearing mice in each treatment group;
[0041] Fig.15 H&E, Ki67, and TUNEL staining results of H22 tumor sections in different treatment groups;
[0042] Fig.16 is the in vivo degradation of different hydrogels over time;
[0043] Fig.17 Figure 2 is the histopathological analysis of skin tissue sections corresponding to the in vivo degradation study. DETAILED DESCRIPTION
[0044] The present invention provides a bismuth iodate oxygen composite piezoelectric hydrogel, which is prepared from raw materials including the following mass percentages:
[0045] The first self-assembling short peptide is 0.125% to 0.5%, the self-assembling stem cell bone marrow homing peptide is 0.125% to 0.5%, the BiOIO3 nanosheet is 0 to 0.02% and the mass percentage of the BiOIO3 nanosheet is not 0, and the solvent is 98.99% to 99.75%; the self-assembling stem cell bone marrow homing peptide is obtained by functionalizing the second self-assembling short peptide with the stem cell bone marrow homing peptide segment.
[0046] In the present invention, the pore size of the bismuth oxyiodate composite piezoelectric hydrogel is preferably 10 to 30 μm, and the porosity is preferably 80% to 90%.
[0047] In the present invention, the storage modulus (G′) of the bismuth oxyiodate composite piezoelectric hydrogel is preferably 30 to 100 Pa, the loss modulus (G″) is preferably 10 to 30 Pa, and the storage modulus is preferably higher than the loss modulus.
[0048] In the present invention, when the shear rate is 0.1s -1 When the shear rate is 100s -1 When the bismuth oxyiodate composite piezoelectric hydrogel has a viscosity of preferably 0 to 10 mPa·s.
[0049] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0050] The mass percentage of the self-assembled stem cell bone marrow homing peptide in the raw materials for preparing the bismuth oxyiodate composite piezoelectric hydrogel provided by the present invention can be 0.125%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.
[0051] In the present invention, the self-assembling stem cell bone marrow homing peptide is obtained by functionalizing a stem cell bone marrow homing peptide segment with a second self-assembling short peptide.
[0052] In the present invention, the stem cell bone marrow homing peptide is preferably the first peptide, the second peptide, the third peptide or the fourth peptide, the amino acid sequence of the first peptide is preferably as shown in SEQ ID NO.1, and the first peptide is preferably EILDVPST derived from fibronectin; the amino acid sequence of the second peptide is preferably as shown in SEQ ID NO.2, and the second peptide is preferably from the leucine-rich repeat protein LRPPRC; the amino acid sequence of the third peptide is preferably as shown in SEQID NO.3, and the third peptide is preferably an artificially designed peptide QHREDGS, the amino acid sequence of the fourth peptide is preferably as shown in SEQ ID NO.4, and the fourth peptide is preferably from the N-terminal sequence PFS (PFSSTKT) of human serum albumin.
[0053] In the present invention, the second self-assembling short peptide is preferably RAD16-I (Ac-RADARADARADARADA-NH2, as shown in SEQ ID NO.6), EAK16-II (Ac-AEAEAKAKAEAEAKAK-NH2, as shown in SEQ ID NO.7), FF (Phe-Phe, Diphenylalanine), VEVK (Ac-VEVKVVEKVEVKVVE-NH2, as shown in SEQ ID NO.5) or KLD-12 (Ac-KLDLKLDLKLDL-NH2, as shown in SEQ ID NO.8).
[0054] The present invention has no particular limitation on the specific preparation method of the self-assembled stem cell bone marrow homing peptide. In a specific embodiment of the present invention, it is synthesized and purified by SciLight Biotechnology, LLC (Scilight-Peptide Co., Ltd. (Beijing, China)).
[0055] The mass percentage of the first self-assembling short peptide in the raw material for preparing the bismuth oxyiodate composite piezoelectric hydrogel provided by the present invention can be 0.125%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.
[0056] In the present invention, the type range of the first self-assembling short peptide is preferably the same as that of the second self-assembling short peptide, which will not be described in detail herein.
[0057] In the present invention, the characteristics of the first self-assembling short peptide and the second self-assembling short peptide include: amino acid sequence dependence, controllability, spontaneous formation of stable nanostructures, reversibility, biocompatibility and low toxicity, multifunctionality, ability to form hydrogels and sensitivity to the environment. By regulating the amino acid sequence and environmental conditions, precise control of the self-assembling short peptides can be achieved, which makes them have broad application potential in the fields of biomaterials, drug delivery and tissue engineering.
[0058] In the present invention, the stem cell bone marrow homing peptide segment is preferably the third peptide segment, and the first self-assembling short peptide and the second self-assembling short peptide are preferably KLD-12. In this case, the self-assembled stem cell bone marrow homing peptide is recorded as KLD / PFS; KLD-12 is an ion-complementary peptide composed of 12 residues, which can form a supramolecular peptide nanofiber hydrogel that simulates the natural extracellular matrix. This hydrogel composed of amino acids is biocompatible and can minimize the formation of toxic by-products; and the functional peptide sequence PFS is a bone marrow homing peptide with excellent ability to home to the bone marrow and bind to stem cells.
[0059] When the self-assembled stem cell bone marrow homing peptide is KLD / PFS, two glycine residues are preferably introduced into the KLD / PFS as connectors to increase the flexibility of the functional epitope, and the formed stem cell bone marrow homing peptide segment is KLD-PFS (Ac-KLDLKLDLKLDLGGPFSSTKT-NH2, as shown in SEQ ID NO.9).
[0060] In the present invention, the mass percentage of BiOIO3 nanosheets in the raw material is preferably 0.005% to 0.01%, specifically 0.005% or 0.01%.
[0061] In the present invention, the particle size of the BiOIO3 nanosheet is preferably 100 to 800 nm, specifically 100, 200, 300, 400, 500, 600, 700 or 800 nm, the thickness is preferably 2 to 6 nm, specifically 2, 4 or 6 nm, and the specific surface area is preferably 10 to 20 m 2 / g; the BiOIO3 nanosheet is a nanomaterial with piezoelectric catalytic effect, has unique two-dimensional structural characteristics, ultra-high surface area and obvious lattice fringes, and the crystal structure is highly ordered and has good crystallinity.
[0062] The present invention has no particular limitation on the source of the BiOIO3 nanosheets, and the nanosheets can be prepared in a manner well known to those skilled in the art. In a specific embodiment of the present invention, the method for preparing the BiOIO3 nanosheets comprises the following steps:
[0063] Bi(NO3)3·5H2O powder, polyvinyl pyrrolidone (PVP) powder and potassium iodate (KIO3) powder are added to ultrapure water and ultrasonically treated until all solid powders are completely dissolved. The mixture is then stirred at room temperature. The resulting uniformly dispersed suspension is added to a polytetrafluoroethylene liner and heated at 120°C for 4 hours to obtain white nanosheets. After the sample is naturally cooled, the upper layer solution is transferred to a centrifuge tube and centrifuged at a low speed for 5 minutes to discard large particle precipitates. The mixture is then centrifuged at a high speed for 10 minutes. The product is centrifuged with ultrapure water and the material is washed three times. Finally, the obtained product is dispersed in water and freeze-dried to obtain the BiOIO3 nanosheets.
[0064] In the present invention, the mass ratio of the Bi(NO3)3·5H2O powder, PVP powder and KIO3 powder is preferably (2-3):1:(1-3), specifically 2:1:1, 3:1:1, 2:1:3 or 3:1:3.
[0065] In the present invention, the rotation speed of the low-speed centrifugation is preferably 1500-3000 rpm, specifically 1500, 2000, 2500 or 3000 rpm, and the time is preferably 5 minutes to discard large particle precipitation; the rotation speed of the high-speed centrifugation is preferably 12000-15000 rpm, specifically 12000, 13000, 14000 or 15000 rpm, and the time is preferably 10 minutes.
[0066] In the present invention, the washing is preferably performed with deionized water, and the number of washings is preferably 3 to 5 times, specifically 3, 4 or 5 times.
[0067] In the present invention, the freeze-drying time is preferably 24 hours. The present invention has no particular limitation on the freeze-drying temperature as long as the water can be completely removed.
[0068] In the present invention, the solvent is PBS buffer, water or cell culture medium.
[0069] In the present invention, the water is preferably ultrapure water.
[0070] In the present invention, the pH value of the PBS buffer is preferably 7.2-7.4.
[0071] In the present invention, the cell culture medium is preferably DMEM culture medium, RPMI 1640 culture medium or bone marrow mesenchymal stem cell complete culture medium.
[0072] The present invention also provides a method for preparing the bismuth oxyiodate composite piezoelectric hydrogel described in the above technical solution, comprising the following steps:
[0073] Mixing the first self-assembling short peptide and the first solvent to obtain a self-assembling short peptide solution;
[0074] mixing the self-assembled stem cell bone marrow homing peptide with a second solvent to obtain a self-assembled stem cell bone marrow homing peptide solution;
[0075] The self-assembled short peptide solution, the self-assembled stem cell bone marrow homing peptide solution, the BiOIO3 nanosheets and the remaining solvent are mixed and then gelled to obtain the bismuth oxygen iodate composite piezoelectric hydrogel.
[0076] The present invention mixes the first self-assembling short peptide and the first solvent to obtain a self-assembling short peptide solution.
[0077] In the present invention, the concentration of the self-assembling short peptide solution is preferably 0.25% to 1% (w / v, g / mL), specifically 0.25%, 0.5% or 1% g / mL. Limiting the concentration of the self-assembling short peptide solution to this range allows gelation.
[0078] In the present invention, the mixing is preferably ultrasonic, and the ultrasonic time is preferably 20 to 40 minutes.
[0079] The invention mixes the self-assembled stem cell bone marrow homing peptide with the second solvent to obtain the self-assembled stem cell bone marrow homing peptide solution.
[0080] In the present invention, the concentration of the self-assembled stem cell bone marrow homing peptide solution is preferably 0.25% to 1% (w / v, g / mL), specifically 0.25%, 0.5% or 1% g / mL. Limiting the concentration of the self-assembled stem cell bone marrow homing peptide solution to this range enables gelation.
[0081] In the present invention, the mixing is preferably ultrasonic, and the ultrasonic time is preferably 20 to 40 minutes.
[0082] After obtaining the self-assembled stem cell bone marrow homing peptide solution and the self-assembled short peptide solution, the present invention mixes the self-assembled short peptide solution, the self-assembled stem cell bone marrow homing peptide solution, BiOIO3 nanosheets and the remaining solvent and then gelates them to obtain the bismuth oxide iodate composite piezoelectric hydrogel.
[0083] In the present invention, the volume ratio of the self-assembling short peptide solution to the self-assembling stem cell bone marrow homing peptide solution is preferably 1:1.
[0084] In the present invention, the BiOIO3 nanosheets and the remaining solvent are preferably first mixed to obtain a BiOIO3 solution, and then the self-assembled short peptide solution, the self-assembled stem cell bone marrow homing peptide solution and the BiOIO3 solution are mixed to perform the gelation.
[0085] In the present invention, the concentration of the BiOIO3 solution is preferably 1 to 1000 μg / mL, more preferably 100 to 400 μg / mL, and specifically may be 100, 200, 300 or 400 μg / mL.
[0086] In the present invention, the gelation is preferably carried out under ultrasonic conditions, and the gelation time is preferably 10 to 30 minutes, specifically 10, 20 or 30 minutes.
[0087] In the present invention, the power of the ultrasound is preferably 200-600W, specifically 200, 300, 400, 500 or 600W.
[0088] After the gelation is completed, the present invention preferably refrigerates the obtained gel product at 2-8°C until it is needed, specifically at 2, 4, 6 or 8°C.
[0089] The present invention also provides the use of the bismuth oxyiodate composite piezoelectric hydrogel described in the above technical scheme or the bismuth oxyiodate composite piezoelectric hydrogel prepared by the preparation method described in the above technical scheme in the preparation of drugs for inhibiting liver cancer, drugs for residual tumors after surgery, or drugs for repairing bone defects.
[0090] In the present invention, the drug for inhibiting residual tumors after surgery and the drug for repairing bone defects independently contain an effective dose of the bismuth iodate oxycomplex piezoelectric hydrogel and an auxiliary agent, wherein the auxiliary agent includes one or more of an auxiliary material, an excipient, and a diluent. The present invention does not specifically limit the specific types of the auxiliary materials, excipients, and diluents, and the types familiar to those skilled in the art can be used.
[0091] In the present invention, the dosage forms of the drug for inhibiting postoperative residual tumors and the drug for repairing bone defects independently include tablets, injections, capsules, granules, pills, powders, oral liquids, sustained-release preparations, controlled-release preparations or nano-preparations that are pharmaceutically acceptable.
[0092] In the present invention, the drug for inhibiting postoperative residual tumor is preferably a drug for inhibiting osteosarcoma.
[0093] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0094] raw material:
[0095] Bi(NO3)3·5H2O, ≥99.99wt%, Aladdin Corporation.
[0096] Polyvinylpyrrolidone, Aladdin Corporation.
[0097] Potassium iodate, Aladdin Corporation.
[0098] The self-assembling peptides KLD-12 (Ac-KLDLKLDLKLDL-NH2) and KLD-PFS (Ac-KLDLKLDLKLDLGGPFSSTKT-NH2) (purity greater than 95%) were synthesized and purified by SciLight Biotechnology, LLC, Scilight-Peptide Co., Ltd. (Beijing, China).
[0099] Example 1
[0100] Preparation of bismuth iodate oxide composite piezoelectric hydrogel (PFS@BiOIO3 NSs) and KLD@BiOIO3 NSs
[0101] 1.5mmol Bi(NO3)3·5H2O powder, 1.5mmol KIO3 powder and 0.3g PVP powder were mixed to prepare a mixture. The mixture was then dissolved in 75mL deionized water and ultrasonically treated for 20min. Subsequently, the uniformly dispersed suspension was transferred to a 100mL polytetrafluoroethylene liner after stirring at room temperature for 4h, and then placed in a hydrothermal reactor for reaction (heating at 120℃ for 4h). After the reaction product was cooled naturally, the supernatant was transferred to a centrifuge tube and centrifuged at 3000rpm for 5min, and then repeated at 13000rpm for 10min. The obtained solid product was washed 3 times with deionized water and then freeze-dried for 24h to obtain BiOIO3 nanosheets.
[0102] Characterization of BiOIO3 nanosheets
[0103] Figure 1 TEM image of BiOIO3 NSs. Figure 2 HRTEM image of BiOIO3 NSs. Figure 3 is the XRD pattern of BiOIO3 NSs. Figure 1 Transmission electron microscopy images show that BiOIO3 nanosheets have unique two-dimensional structural characteristics and ultra-high surface area (specific surface area of 20m 2 / g), Figure 2 High-resolution transmission electron microscopy revealed distinct lattice fringes with interplanar spacings of 0.238 nm (d(200)) and 0.287 nm (d(002)), indicating that the BiOIO3 NSs crystal structure is highly ordered. Figure 3 The X-ray diffraction pattern matches well with the standard PDF data (PDF#97-026-2019), confirming that the sample is a single phase of BiOIO3 NSs, indicating that the sample has good crystallinity.
[0104] Dissolve 10 mg of KLD-12 self-assembling polypeptide in 1 mL of ultrapure water to prepare a 1% (w / v, g / mL) KLD solution; dissolve 10 mg of KLD-PFS self-assembling stem cell bone marrow homing peptide in 1 mL of ultrapure water to prepare a 1% (w / v, g / mL) KLD-PFS solution; take 500 μL of KLD solution and mix with 500 μL of KLD-PFS solution to prepare a PFS solution.
[0105] 1 mL of KLD solution and 1 mL of PFS solution were mixed with 1 mL of BiOIO3 NSs dispersion (concentration of 400 μg / mL) to obtain injectable KLD@BiOIO3 NSs solution and PFS@BiOIO3 NSs solution, respectively. The KLD@BiOIO3 NSs solution and PFS@BiOIO3 NSs solution were gelled by ultrasonication (500W) for 10 min, respectively. The prepared gel was refrigerated at 4°C and taken out when needed to obtain KLD@BiOIO3 NSs and PFS@BiOIO3 NSs, respectively. The obtained PFS@BiOIO3 NSs was prepared from the following raw materials in mass percentage: 0.25% of the first self-assembled short peptide KLD, 0.25% of the self-assembled stem cell bone marrow homing peptide KLD-PFS, 0.02% of BiOIO3 nanosheets, and 99.48% of water.
[0106] Comparative Example 1
[0107] The KLD solution in Example 1 was taken and subjected to gelation by ultrasonication (500 W) for 10 min. The prepared gel was refrigerated at 4° C. until it was needed, thereby obtaining a KLD gel.
[0108] Comparative Example 2
[0109] The PFS solution in Example 1 was taken and subjected to gelation by ultrasound (500 W) for 10 min. The prepared gel was refrigerated at 4° C. until it was needed, thereby obtaining a PFS gel.
[0110] Figure 4 TEM images of each group of hydrogels show that the nanofiber network of the hydrogel securely encapsulates BiOIO3NSs; Figure 5 Cryo-SEM image of KLD hydrogel. Figure 6 Cryo-SEM image of KLD@BiOIO3 NSs hydrogel. Figure 7 Cryo-SEM image of PFS hydrogel. Figure 8 This is the Cryo-SEM image of the PFS@BiOIO3NSs composite piezoelectric hydrogel. It can be seen that the surface of the hydrogel without BiOIO3 NSs is smooth, while the surface roughness of the hydrogel containing BiOIO3 NSs increases, and the porous structure of the hydrogel surface. From the results of the transmission electron microscopy regional element distribution map, it can be seen that the Bi, I, and O elements of BiOIO3 NSs are uniformly distributed in the PFS hydrogel, indicating that the PFS@BiOIO3 NSs composite piezoelectric hydrogel was successfully constructed.
[0111] Piezoelectric properties of BiOIO3 NSs
[0112] The piezoelectric response performance of the BiOIO3 NSs prepared in Example 1 was evaluated using piezoelectric force microscopy (PFM). Fig. 9 The characteristic butterfly loop and phase hysteresis curves of BiOIO3 NSs under ±10V voltage show that under ±10V applied voltage, BiOIO3 NSs shows characteristic amplitude butterfly loop and phase hysteresis, and the calculated piezoelectric coefficient (d33) is 21.1pm / V.
[0113] The rheological parameters of each group of hydrogels in Example 1 were tested. Fig.10 Rheological property curves of each group of hydrogels. It can be seen that the storage modulus (G′) of the four hydrogel samples (KLD, PFS, KLD@BiOIO3 NSs and PFS@BiOIO3NSs) is higher than the loss modulus (G″), showing gel-like behavior. The specific data are: KLD: G′: 10~30Pa, G″: 1~10Pa; PFS: G′: 30~100Pa, G″: 10~30Pa; KLD@BiOIO3NSs: G′: 10~30Pa, G″: 1~10Pa; PFS@BiOIO3 NSs: G′: 30~100Pa, G″: 10~30Pa.
[0114] The rheological properties of the hydrogel were tested using a Haake Mars40 rheometer. The specific steps are as follows: Place the hydrogel sample on the test platform of the rheometer and use parallel plates as fixtures. Set the shear rate range, gradually increasing from a low rate to cover the range where shear thinning may occur. Record the viscosity values at different shear rates, and analyze whether the hydrogel has shear thinning behavior by plotting a logarithmic curve of shear rate and viscosity. If the viscosity decreases significantly with increasing shear rate, it means that the material has shear thinning properties. Fig.11 The static shear rate curves of each group of hydrogels show that the four groups of hydrogels have the characteristics of shear thinning, and the viscosity decreases with the increase of shear rate. The PFS@BiOIO3 NSs piezoelectric hydrogel can be squeezed out through a syringe to form stable "WMU" letters. Fig.11 The left picture in the middle illustration is horizontal placement, and the right picture is vertical placement, which shows that the formed piezoelectric hydrogel has good stability and does not flow and deform due to vertical placement. Storage conditions: Place at room temperature for 5 minutes.
[0115] Example 2
[0116] The same as Example 1, the only difference is that the concentration of the BiOIO3 NSs dispersion is adjusted to 50 μg / mL, and a gel with a safe concentration is prepared, including KLD@BiOIO3 NSs and PFS@BiOIO3NSs with a safe concentration.
[0117] In vitro tumor killing effect
[0118] When conducting cell experiments, we first prepare cell culture medium containing BiOIO3 at gradient concentrations and incubate the cells. We then use the CCK8 kit to detect cell viability. The concentration at which cell viability is maintained above 80% (compared to the untreated group) can be considered a safe concentration. At a safe concentration, the nanomaterial will not cause significant toxic reactions in cells, ensuring the reliability and repeatability of the experiment.
[0119] In order to explore the tumor killing ability of piezoelectric stimulation, the hydrogels of each group were incubated with safe concentrations for 24 h (37 °C, 5% CO2) and then ultrasonically treated (1.0 MHz, 1.0 W cm 2 , 50% duty cycle, US) mouse K7M2 osteosarcoma osteoblasts (from ATCC cell bank), and cells without any treatment were used as negative control. Fig.12 Figure 2 are fluorescence microscope images of live / dead tumor cells after treatment with different conditions, namely G1: control group, G2: KLD hydrogel group, G3: KLD@BiOIO3NSs hydrogel group, G4: PFS@BiOIO3 NSs hydrogel group, G5: PFS hydrogel + US treatment group, G6: KLD@BiOIO3NSs hydrogel + US treatment group, G7: PFS@BiOIO3 NSs hydrogel + US treatment group. The results showed that the groups treated with KLD@BiOIO3NSs+US and PFS@BiOIO3 NSs+US showed good anti-tumor effects, and the effect of the group treated with PFS@BiOIO3 NSs+US was slightly better than that of the group treated with KLD@BiOIO3NSs+US. It can be seen that BiOIO3 NSs+US-mediated tumor piezoelectric catalytic therapy can effectively kill K7M2 osteosarcoma cells.
[0120] In vitro studies on promoting bone mineralization
[0121] The osteogenic differentiation of bone marrow mesenchymal stem cells requires a large amount of energy for collagen biosynthesis, bone matrix protein and mineral deposition. On the basis of efficient killing of K7M2 osteosarcoma cells, the regulatory effect of piezoelectric stimulation on osteogenic differentiation of different hydrogels was further explored. The mRNA expression of early osteogenic-related genes ALP, BMP-2, and Runx2, and the mRNA expression of late OCN, BMP-2, and OPN were determined to study the regulatory effect of PFS@BiOIO3 NSs on osteogenic-related genes. The Transwell method was used to co-culture mesenchymal stem cells (MSCs) between different groups (gels were placed in the upper chamber and cells were cultured in the lower chamber). The cells in the lower chamber were collected after 7 days of culture in the first batch, and the expression of ALP, BMP-2 and Runx2 was detected. The expression of OPN, BMP-2 and OCN was detected after 14 days of culture in the second batch. The total RNA of bone marrow mesenchymal stem cells (BMSCs) in each group was extracted by RNA rapid purification kit, and HiScript III RT SuperMix was used to reverse transcribe and generate cDNA for subsequent qPCR analysis. qPCR reactions were performed using ChamQUniversal SYBR qPCR MasterMix. GAPDH was used as an internal reference gene, and the relative gene expression was calculated using the 2-ΔΔCt method. Fig.13 Figure 2 shows the expression of genes related to early / late osteogenic differentiation in different treatment groups, namely G1: control group, G2: KLD hydrogel group, G3: KLD@BiOIO3 NSs hydrogel group, G4: PFS@BiOIO3 NSs hydrogel group, G5: PFS hydrogel + US treatment group, G6: KLD@BiOIO3 NSs hydrogel + US treatment group, G7: PFS@BiOIO3 NSs hydrogel + US treatment group. It can be seen that on the 7th day, the expression levels of ALP, BMP-2 and Runx2 in the PFS+US and PFS@BiOIO3 NSs+US groups were significantly higher than those in the other groups. Similarly, on the 14th day, the expression levels of OCN, BMP-2 and OPN were significantly increased. This indicates that the combination of PFS and BiOIO3 NSs significantly improved osteogenic activity under the enhancement of US. The important role of this synergistic effect in the expression of early and late osteogenic genes indicates its potential application in bone tissue engineering and bone repair.
[0122] In vivo testing of tumor growth inhibition and osteogenesis promotion
[0123] Four-week-old Balb / c female mice (weighing approximately 20 g) were purchased from Beijing Weitonglihua Experimental Animal Technology Co., Ltd. and were adaptively raised in an SPF-grade experimental animal room for one week before subsequent experimental procedures began.
[0124] An orthotopic osteosarcoma tumor model was established by injecting K7M2 cells into the bone marrow cavity of mice through the tibial plateau. When the tumor volume reached ∼150 mm 3 At the same time, the mice were randomly divided into 8 groups for treatment (including S: sham group (animals received the same anesthesia and surgical procedures as the experimental group, injected with normal saline, but no core intervention, as a control to evaluate the effect of the surgery itself on the experimental results), G1: control group, G2: KLD hydrogel group, G3: KLD@BiOIO3 NSs hydrogel group, G4: PFS@BiOIO3 NSs hydrogel group, G5: PFS hydrogel + US treatment group, G6: KLD@BiOIO3 NSs hydrogel + US treatment group, G7: PFS@BiOIO3 NSs hydrogel + US treatment group). Intratumoral injection treatment was performed every 4 days, with multiple injections in the tumor and near the tibia, and the injection volume was 100 μL, and tumor growth was monitored. The parameters of US ultrasound treatment were set at 1.0 MHz, 1.0 W / cm 2 , 50% duty cycle, 5 min, the monitoring results showed that the tumor growth in the KLD@BiOIO3NSs hydrogel+US ultrasound group and the PFS@BiOIO3NSs hydrogel+US treatment group was significantly inhibited. Fig.14 As shown in the figure, after 5 treatments and 20 days after the first treatment, the condition of the osteosarcoma tibia was evaluated by micro-CT observation, and the tibia was recorded by cross-sectional (X), longitudinal (Y) and three-dimensional (3D) reconstruction. Except for the sham operation group, the remaining bone tissues showed varying degrees of tumor invasion and erosion, while the PFS@BiOIO3NSs hydrogel+US treatment group had the least damage. This is because the BiOIO3NSs hydrogel+US treatment and the tumoricidal effect of PFS hydrogel promoted the recruitment, proliferation and differentiation of bone marrow mesenchymal stem cells (BMSCs), thereby promoting bone regeneration.
[0125] Inhibitory effects on different tumors
[0126] To study the wide applicability of different hydrogels in tumor treatment, a subcutaneous HCC mouse model was established. H22 cells were implanted subcutaneously on the ventral side of the mouse. One week later, when the tumor volume reached ∼100 mm 3 The mice were randomly divided into 7 groups for different treatments, namely G1: control group, G2: KLD hydrogel group, G3: KLD@BiOIO3 NSs hydrogel group, G4: PFS@BiOIO3 NSs hydrogel group, G5: PFS hydrogel + US treatment group, G6: KLD@BiOIO3 NSs hydrogel + US treatment group and G7: PFS@BiOIO3NSs hydrogel + US treatment group. Intratumoral injection treatment was performed every 2 days, with multiple injections in the tumor, and each injection volume was 100 μL). The US parameters were set as: 1.0 MHz, 1.0 W / cm2 , 50% duty cycle, 5 min, and tumor growth was monitored until the 17th day.
[0127] The tumor sections of each group were stained with H&E, Ki67 and TUNEL. Fig.15 The results of H&E, Ki67 and TUNEL staining of H22 tumor sections show that both KLD@BiOIO3NSs+US group and PFS@BiOIO3NSs+US group can effectively inhibit tumors and prolong survival. Ki67 and TUNEL positive areas show that in the treatment groups KLD@BiOIO3NSs+US group and PFS@BiOIO3 NSs+US group, tumor cell proliferation is reduced, and cell apoptosis and necrosis are severe.
[0128] Verification of the degradability of the prepared PFS@BiOIO3 NSs:
[0129] PFS@BiOIO3 NSs were injected into the subcutaneous cavity of Balb / c mice using a 1 mL sterile syringe. The mouse skin tissue was peeled off at sampling time points of 0h, 24h, and 48h after injection, and photos were taken to record the degradation of the hydrogel. The removed skin tissue was then fixed, embedded, and sectioned for histopathological H&E staining analysis to evaluate tissue reaction, inflammation, and biocompatibility.
[0130] Fig.16 is the in vivo degradation of different hydrogels over time. Fig.17 The figure is a histopathological analysis diagram of skin tissue sections corresponding to the in vivo degradation study. It can be seen that the bismuth iodate composite piezoelectric hydrogel of the present invention can be rapidly degraded in mice and only causes a mild inflammatory reaction, indicating that it has good biocompatibility.
[0131] Comparative Example 3
[0132] Dissolve 10 mg of KLD-12 self-assembling polypeptide in 10 mL of ultrapure water to prepare a 0.1% (w / v, g / mL) KLD solution; dissolve 10 mg of KLD-PFS self-assembling stem cell bone marrow homing peptide in 10 mL of ultrapure water to prepare a 0.1% (w / v, g / mL) KLD-PFS solution; take 500 μL of KLD solution and mix with 500 μL of KLD-PFS solution to prepare a PFS solution.
[0133] 1 mL of PFS solution was mixed with 1 mL of BiOIO3 NSs (concentration of 400 μg / mL) to obtain a PFS@BiOIO3 NSs solution. The mixture was subjected to ultrasound (500 W) for 10 min for gelation. After ultrasound treatment, it could not crosslink to form an injectable hydrogel. The reason was that in the preparation raw materials of this comparative example, the mass percentage of KLD-PFS was 0.025%, the mass percentage of KLD was 0.025%, the mass percentage of BiOIO3 nanosheets was 0.02%, and the mass percentage of solvent was 99.93%. The solvent accounted for too high a proportion and could not form a gel.
[0134] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A bismuth iodate composite piezoelectric hydrogel, characterized in that: It is prepared from the following raw materials in percentage by weight: The first self-assembling short peptide is 0.125% to 0.5%, the self-assembling stem cell bone marrow homing peptide is 0.125% to 0.5%, the BiOIO3 nanosheet is 0 to 0.02% and the mass percentage of the BiOIO3 nanosheet is not 0, and the solvent is 98.99% to 99.75%; the self-assembling stem cell bone marrow homing peptide is obtained by functionalizing the second self-assembling short peptide with the stem cell bone marrow homing peptide segment.
2. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 1, characterized in that: The stem cell bone marrow homing peptide segment is a first peptide segment, a second peptide segment, a third peptide segment or a fourth peptide segment, the amino acid sequence of the first peptide segment is shown as SEQ ID NO.1, the amino acid sequence of the second peptide segment is shown as SEQ ID NO.2, the amino acid sequence of the third peptide segment is shown as SEQ ID NO.3, and the amino acid sequence of the fourth peptide segment is shown as SEQ ID NO.
4.
3. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 1 or 2, characterized in that: The first self-assembling short peptide and the second self-assembling short peptide are independently RAD16-I, EAK16-II, FF, VEVK or KLD-12, and the amino acid sequence of VEVK is shown in SEQ ID NO.
5.
4. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 2, characterized in that: The stem cell bone marrow homing peptide segment is the third peptide segment, and the first self-assembling short peptide and the second self-assembling short peptide are both KLD-12.
5. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 1, characterized in that: The mass percentage of BiOIO3 nanosheets in the raw material is 0.005% to 0.01%.
6. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 1, characterized in that: The particle size of the BiOIO3 nanosheet is 100-800 nm, the thickness is 2-6 nm, and the specific surface area is 10-20 m 2 / g.
7. The bismuth oxyiodate composite piezoelectric hydrogel according to claim 1, characterized in that: The solvent is PBS buffer, water or cell culture medium.
8. The method for preparing the bismuth oxyiodate composite piezoelectric hydrogel according to any one of claims 1 to 7, characterized in that: The following steps are involved: Mixing the first self-assembling short peptide and the first solvent to obtain a self-assembling short peptide solution; mixing the self-assembled stem cell bone marrow homing peptide with a second solvent to obtain a self-assembled stem cell bone marrow homing peptide solution; The self-assembled short peptide solution, the self-assembled stem cell bone marrow homing peptide solution, the BiOIO3 nanosheets and the remaining solvent are mixed and then gelled to obtain the bismuth oxygen iodate composite piezoelectric hydrogel.
9. The preparation method according to claim 8, characterized in that: The gelation is carried out under ultrasonic conditions, and the gelation time is 10 to 30 minutes.
10. Use of the bismuth oxyiodate composite piezoelectric hydrogel according to any one of claims 1 to 7 or the bismuth oxyiodate composite piezoelectric hydrogel prepared by the preparation method according to claim 8 or 9 in the preparation of anti-liver cancer drugs, drugs for inhibiting residual tumors after surgery, or drugs for repairing bone defects.
Citation Information
Patent Citations
BaTiO3 composite piezoelectric hydrogel as well as preparation method and application thereof
CN117883632A
Cited By
Piezoelectric hydrogel loaded with response polypeptide and application thereof
CN121513197A
A piezoelectric hydrogel loaded with a response polypeptide and application thereof
CN121513197B